Działalność naukowa Biblioteki Głównej Uniwersytetu Pedagogicznego w Krakowie - Piotrowska, Ewa (Biblioteka Uniwersytecka w Poznaniu, 2018)
W artykule przedstawiono realizację zadań naukowych w systemie biblioteczno-informacyjnym Uniwersytetu Pedagogicznego w Krakowie (UP). Zaprezentowano zakres czynności na stanowisku sekretarza naukowego Biblioteki Głównej UP oraz obowiązujące na uczelni zasady powoływania osób na stanowiska bibliotekarzy dyplomowanych. Poddano analizie różne formy działalności naukowej: organizowane w bibliotece konferencje, seminaria, warsztaty dla bibliotekarzy, czasopismo elektroniczne i monografie wydawane przez bibliotekę, publikacje naukowe bibliotekarzy, udział w projektach, współpraca z bibliotekami zagranicznymi.

The article presents the implementation of scientific tasks in the library and information system of the Pedagogical University of Kraków (PU). The scope of activities as the scientific secretary of the Main Library of the PU and the rules for appointing people to the positions of certified librarians at the university were presented. Different forms of scientific activity were analyzed: conferences organized in the library, seminars, workshops for librarians, an electronic journal and monographs published by the library, scientific publications of librarians, participation in projects, cooperation with foreign libraries.
Scientific activity of the Main Library of the Pedagogical University of Kraków
Keywords: biblioteka akademicka; academic library; biblioteka naukowa; scientific library; scientific activity of libraries; działalność naukowa bibliotek; librarians of the scientific library; bibliotekarze biblioteki naukowej